1985
DOI: 10.1227/00006123-198506000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysms of the Distal Posterior Inferior Cerebellar Artery: Experience with Three Cases and Review of the Literature

Abstract: We report 3 surgically treated aneurysms of the distal posterior inferior cerebellar artery (PICA) and review 36 cases in the literature. More than half of the distal PICA aneurysms arose distal to the choroidal arch. These lesions often arose at a turning point (i.e., a hairpin curve) of an artery instead of at a junction of vessels. Distal PICA aneurysms are likely to be missed and it is necessary to investigate carefully with four-vessel angiography even if computed tomography is done. Eighty-two per cent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…1,2 Only case reports or small case series have been published, and no precise information is available in the literature regarding the management of distal cerebellar artery aneurysms or the associated long-term results. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Several approaches have been proposed to surgically treat these aneurysms, depending on their size and location. Although direct clipping is possible in some cases, sophisticated surgical techniques such as hypothermic cardiac arrest and bypass construction are often needed.…”
mentioning
confidence: 99%
“…1,2 Only case reports or small case series have been published, and no precise information is available in the literature regarding the management of distal cerebellar artery aneurysms or the associated long-term results. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Several approaches have been proposed to surgically treat these aneurysms, depending on their size and location. Although direct clipping is possible in some cases, sophisticated surgical techniques such as hypothermic cardiac arrest and bypass construction are often needed.…”
mentioning
confidence: 99%
“…The pathogenesis of aneurysms in PICA is matter of discussion. It is well accepted that the site of prediction of general aneurysms are the arterial bifurcations; however, the great majority of aneurysms at the distal PICA are not related to its branches [3][4][5][6] . Hemodynamic stress at the hairpin curve of the PICA may play a role in branchless aneurysm formation 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of them are localized at the vertebral artery (VA) PI-CA junction [3][4][5] . There are few large series of distal PICA aneurysms [6][7] , with no more than 26 cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many small arteries arise from the medullary segment and go through the brainstem, so the aneurysm's location is important in the selection of which procedure-clipping or trapping-to use. If neck clipping had been difficult, we would have used proximal ligation or trapping3, 5,17,19,22,25) Hudgins et a1.3 and Lister et al 17 have reported that aneurysms arising from, or distal to, the telovelotonsillar segment might be treated with proximal trappings as brainstem perforators do not arise beyond this point.…”
Section: Discussionmentioning
confidence: 99%